Representative Literal and Nonliteral Speech Acts in Novels “Dear Allah” by Diana Febi: A Sociopragmatic Review - Arifah, Siti; Hodairiyah, Hodairiyah; Azis, Abd (Edumaspul: Jurnal Pendidikan, 2023)
This qualitative descriptive study aims to describe the representation of literal and nonliteral speech acts in the novel "Dear Allah" by Diana Febi. From a theoretical perspective, this research uses a sociopragmatic system or view. While the method or technique of data collection in this research is a documentation study or literature study, in this case, the literature review is in the form of texts contained in the novel Dear Allah by Diana Febi. The novel is the primary data source. Documentation or literature studies are carried out through direct appreciation and rational understanding of the meaning implied in the novel. The results of this study show (1) representative literal speech acts in Diana Febi's novel Dear Allah and (2) representative nonliteral speech acts in Diana Febi's novel Dear Allah. This research makes a scientific contribution, especially in linguistics, on the sociopragmatic aspect so that understanding the implied meaning of a novel can be understood as a whole in terms of social meaning.